Aspects of trypanotolerance and their association with performance in N'Dama cattle - D'Ieteren, G.D.M.; Feron, A.; Kakiese, O.; Kemp, Stephen J.; Maille, J.C.; Teale, A.J.; Trail, J.C.M.; Yangari, G. (Utrecht University, 1990)
A study was conducted to assess the correlation between criteria of trypanotolerance and production. N'dama post weaner cattle with different weights and from different age groups were studied for weight gain, packed cell volume (PCV) and for the presence of trypanosomes. The analysis approach was to simultaneously estimate the phenotypic relationships between parasitaemia aspects, anaemia control aspects and daily liveweight change of the animals.